2005
DOI: 10.1111/j.1365-2036.2006.02742.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: updates in the pathogenesis and therapy of hepatic sinusoidal obstruction syndrome

Abstract: Hepatic sinusoidal obstruction syndrome is frequently linked to high-dose chemotherapy/total-body irradiation in recipients of haematopoietic stem cell transplantation, long-term use of azathioprine after organ transplantation and other chemotherapeutic agents. The incidence of hepatic sinusoidal obstruction syndrome varies from 0% to 70%, and is decreasing. Disease risk is higher in patients with malignancies, hepatitis C virus infection, those who present late, when norethisterone is used to prevent menstrua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
123
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 150 publications
2
123
0
2
Order By: Relevance
“…Iguchi et al observed increased serum levels of VEGF during development of SOS in human patients, 40 leaving open the question of whether VEGF-induced acceleration of vasopermeability, neovascularization, and/or expression of coagulopathic tissue factors on circulating mononuclear cells may play a role in SOS pathogenesis. 32 Nakamura et al 41 hypothesized that antiangiogenic agents may protect against SOS, and chose to use sorafenib to test this hypothesis. Sorafenib is a multiple receptor tyrosine kinase inhibitor that inhibits multiple tyrosine kinases including the VEGF receptor-2 (VEGFR-2) and -3 (VEGFR-3).…”
Section: Experimental Investigation In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iguchi et al observed increased serum levels of VEGF during development of SOS in human patients, 40 leaving open the question of whether VEGF-induced acceleration of vasopermeability, neovascularization, and/or expression of coagulopathic tissue factors on circulating mononuclear cells may play a role in SOS pathogenesis. 32 Nakamura et al 41 hypothesized that antiangiogenic agents may protect against SOS, and chose to use sorafenib to test this hypothesis. Sorafenib is a multiple receptor tyrosine kinase inhibitor that inhibits multiple tyrosine kinases including the VEGF receptor-2 (VEGFR-2) and -3 (VEGFR-3).…”
Section: Experimental Investigation In Animalsmentioning
confidence: 99%
“…Key pathogenic factors include SEC glutathione depletion, nitric oxide depletion, increased expression of matrix metalloproteinases and vascular endothelial growth factor (VEGF), and activation of clotting factors. 32 In the first instance, drugs leading to SOS are metabolized exclusively by the hepatocellular cytochrome P450 systems, for which glutathione is an antioxidant recovery mechanism. Hepatic exposure to these drugs leads to depletion of glutathione.…”
Section: Experimental Investigation In Animalsmentioning
confidence: 99%
“…Abnormalities of liver function were generally transient and reversible. Veno-occlusive disease (VOD) occurred in seven patients (3%), of whom two patients deceased [12]. VOD is the most severe adverse event of GO.…”
Section: Introductionmentioning
confidence: 99%
“…Other important factors are nitric oxide depletion, vasoconstriction, increased expression of matrix metalloproteinase-9 (MMP9) and vascular endothelial growth factor and activation of clotting cascade. [40][41][42][43] Increased expression and release of MMP9is an early change in the pathogenesis of SOS. MMP9 inhibitors have been found to prevent SOS in animal models.…”
Section: Correct Answers: a And Bmentioning
confidence: 99%